ENVISION: A phase 3b/4 randomized, double‐blind, placebo‐controlled, parallel‐group study to verify the clinical benefit of aducanumab in participants with early Alzheimer's disease. (20th December 2022) - Murphy, Jennifer; Aisen, Paul; Barkhof, Frederik; Castrillo‐Viguera, Carmen; Cheng, Wenting; Cohen, Sharon; Hansson, Oskar; He, Ping; Iwatsubo, Takeshi; Jaeger, Judy; Montenigro, Philip H.; Rubel, Carrie E.; et al.
Abstract: Background: Aducanumab is a human monoclonal antibody selective for aggregated forms of amyloid beta approved in the United States by the Food and Drug Administration (FDA) for the treatment of Alzheimer's disease on June 7, 2021 under the accelerated approval pathway, which requires a randomized‐controlled trial with an appropriate control to verify the clinical benefit of aducanumab. On March 25, 2022 the sponsor submitted the final protocol for this trial, named ENVISION, to the FDA. Method: ENVISION (NCT05310071) is a multicenter, randomized, double‐blind, placebo‐controlled, parallel group study in participants with mild cognitive impairment due to Alzheimer's disease (Stage 3) and mild Alzheimer's disease dementia (Stage 4), designed to verify the clinical efficacy and safety of aducanumab. Key enrollment criteria include MMSE score of 22‐30, age 60‐85, CDR‐G of 0.5 or 1.0, regardless of ApoE ε4 status. Participants will be randomized, to receive aducanumab or placebo in a 2:1 ratio and will be titrated to 10 mg/kg aducanumab or placebo by intravenous infusion every 4 weeks for a treatment duration of 24 months. The primary objective is to assess the clinical benefit of monthly doses of aducanumab in slowing cognitive and functional impairment as measured by change of CDR‐SB score at 18 months as compared to placebo. Key secondary endpoints include change in ADCS‐ADL‐MCI, ADAS‐Cog13, iADRS, MMSE, and NPI‐10; other secondary endpoints include change in amyloid PET and tau PET signal. Safety endpoints include incidence of ARIA events and SAEs. Exploratory endpoints include CSF and plasma biomarkers. Approximately 1512 participants will be enrolled across 220 centers globally. A racially/ethnically representative population will be included in the United States, with an enrollment goal of 18% Black/African American and LatinX/Hispanic patients. Result: ENVISION will begin in Q2 2022 and read out approximately 4 years after first patient in. Primary analysis read‐out of clinical, biomarker, and safety data will be at 18 months, with additional longer‐term data on aducanumab treatment effect up to 24 months. Conclusion: The confirmatory ENVISION trial will further explore clinical efficacy, biomarker profile, and safety of aducanumab in a racially/ethnically representative population.